Four Hot Corrosion Resistant Materials for IGT Blades. (2015) - Liu, C.J.; Peng, J.Q.
Abstract: Four hot corrosion resistance alloys, K444, K435, K452, GH4413, were used for IGT blades. This paper described those four alloys for Industrial Gas Turbine (IGT) blades with the chemical composition, hot corrosion resistant properties and long term structure stability. According to the practical manufacture experiences, the eutectic problem of K444 alloy and the effect of solution temperature on the properties of GH4413 were also studied.